2006
DOI: 10.1111/j.1365-294x.2006.03110.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors influence population genetic structure of European grey wolves

Abstract: Although the mechanisms controlling gene flow among populations are particularly important for evolutionary processes, they are still poorly understood, especially in the case of large carnivoran mammals with extensive continuous distributions. We studied the question of factors affecting population genetic structure in the grey wolf, Canis lupus, one of the most mobile terrestrial carnivores. We analysed variability in mitochondrial DNA and 14 microsatellite loci for a sample of 643 individuals from 59 locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
252
5
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(286 citation statements)
references
References 104 publications
22
252
5
2
Order By: Relevance
“…When the results of the current study are added to those of previous studies on this topic (Haughland & Larsen 2004;Sacks et al 2005;Tonnis et al 2005;Pilot et al 2006;Selonen et al 2007), evidence is accumulating that natal experience may play an important role in determining habitat choice for freeliving dispersers in natural landscapes. In light of this evidence, it seems likely that NHPI may impact ecological and evolutionary processes in a variety of species under natural conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the results of the current study are added to those of previous studies on this topic (Haughland & Larsen 2004;Sacks et al 2005;Tonnis et al 2005;Pilot et al 2006;Selonen et al 2007), evidence is accumulating that natal experience may play an important role in determining habitat choice for freeliving dispersers in natural landscapes. In light of this evidence, it seems likely that NHPI may impact ecological and evolutionary processes in a variety of species under natural conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the considerable interest in the broader implications of NHPI, the vast majority of empirical studies of this phenomenon have been conducted in the laboratory and used insects as the experimental subjects (Davis & Stamps 2004;Davis 2006;Stamps & Davis 2006), although a few field studies have reported a population genetic structure consistent with NHPI (Sacks et al 2005;Tonnis et al 2005;Pilot et al 2006). Recently, Haughland & Larsen (2004) found that red squirrels (Tamiasciurus hudsonicus) born in either logged or intact coniferous forests were likely to recruit to new sites that were structurally similar to their natal site.…”
Section: Introductionmentioning
confidence: 99%
“…However, local-scale genetic structure can be detected in different regions of Europe (Pilot et al 2006;Aspi et al 2008;Czarnomska et al 2013) and elsewhere in the species distribution, and appears to be determined mainly by ecological features rather than geographical barriers (e.g. Carmichael et al 2001;Geffen et al 2004;Pilot et al 2006). Earlier genetic studies suggest that Bulgarian wolves contain high levels of genetic diversity compared to elsewhere in Europe (Lucchini et al 2004;Pilot et al 2006Pilot et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on mitochondrial DNA (mtDNA) and microsatellite variability in European wolves revealed haplotype and allele sharing among local populations from distant parts of the continent (Lucchini et al 2004;Pilot et al 2006Pilot et al , 2010. However, local-scale genetic structure can be detected in different regions of Europe (Pilot et al 2006;Aspi et al 2008;Czarnomska et al 2013) and elsewhere in the species distribution, and appears to be determined mainly by ecological features rather than geographical barriers (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation